2008
DOI: 10.1007/978-3-540-87744-8_44
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Analysis of Online Bin Coloring Algorithms Via Stochastic Comparison

Abstract: This paper proposes a new method for probabilistic analysis of online algorithms that is based on the notion of stochastic dominance. We develop the method for the Online Bin Coloring problem introduced in [15]. Using methods for the stochastic comparison of Markov chains we establish the strong result that the performance of the online algorithm GreedyFit is stochastically dominated by the performance of the algorithm OneBin for any number of items processed. This result gives a more realistic picture than co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…We show that, according to the strict relative worst-order ratio, GF is better than OB. Interestingly, a related result was given by Hiller and Vredeveld [15] who showed that GF is better than OB, using probabilistic analysis.…”
Section: Bin Coloringmentioning
confidence: 80%
See 2 more Smart Citations
“…We show that, according to the strict relative worst-order ratio, GF is better than OB. Interestingly, a related result was given by Hiller and Vredeveld [15] who showed that GF is better than OB, using probabilistic analysis.…”
Section: Bin Coloringmentioning
confidence: 80%
“…The bin covering problem [1,11,8,15] is in some sense the opposite of the bin packing problem as we now want to maximize the number of bins containing items of a total size of at least one. The Harmonic algorithms for this problem are the same as for standard bin packing, except that a bin is closed only when the total size of the items in the bin reaches at least one.…”
Section: Bin Coveringmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that for both paging anf list update, randomization helps in inproving the performance of algorithms, and a variety of randomized algorithms have been proposed and analyzed. Very recently, Hiller and Vredeveld [23] use the notion of stochastic dominance in the context of probabilistic analysis of online bin coloring algorithms. We believe that both these two types of analysis could be useful in studying the effect of randomization in online computation, since they are closely related.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Hiller and Vredeveld [19] use the notion of stochastic dominance in the context of probabilistic analysis of online bin coloring algorithms. We believe that both these two types of analysis could be useful in studying the effect of randomization in online computation, since they are closely related.…”
Section: Future Workmentioning
confidence: 99%